Research data for dissertation project "The dynamic preferences and incentives of natural resource users" - Schaap, Robbert (Universität, 2021)
Contained in this datset are the data from the surveys in Chile and Tanzania and the replication files for the analysis conducted in the doctoral dissertation: "The dynamic preferences and incentives of natural resource users". The project is centered around the management of natural resources and the behaviours of resource users, such as small-scale fishers. The papers within the dissertation touch on subjects such as endogenous risk- and social preference, prudence, precautionary savings and social norms of cooperation. (2020-09-30)
Gesehen am 07.07.2021
Keywords: Forschungsdaten; Datenbank